Penerapan Terapi Akupresur Pada Asuhan Keperawatan Dengan Diabetes Melitus Tipe 2 - Kevan Vincen Marupah; Yuanita Panma (AKPER Pasar Rebo, 2024)
Diabetes mellitus is a metabolic disease characterized by increased blood sugar levels caused by abnormalities in insulin secretion. Increased blood sugar levels can cause various complications that can reduce the patient's quality of life. Acupressure is one of the independent nursing interventions to lower blood sugar levels. This research method uses a descriptive method with a case study approach accompanied by the application of evidence-based practice. Nursing care was carried out on a 67-year-old male patient with a medical diagnosis of diabetes mellitus. From the results of the assessment, five nursing problems were obtained, namely the risk of decreased cardiac output, the risk of unstable blood glucose levels, the risk of nutritional deficits, acute pain, and fatigue. Acupressure therapy was carried out at points SP-6 and ST-36 for 10 minutes on each foot with a frequency of 2x/day for three days. The evaluation results showed a decrease in blood glucose levels from 143 mg/dl in the initial assessment to 121 mg/dl on the third day of implementation. It can be concluded that acupressure techniques can be applied to patients with type 2 diabetes mellitus to lower blood glucose levels.